Theory and facts in proof, that the laws for the imposition of tithes are attended with the most calamitous consequences to the country, with plans for the redemption of tithes, and a comparison of the effects of a repeal of the tithe lawes, with a proposed repeal of the corn lawes (Hatchard and Son, 1826)
With appendix.